Deconstructive Analysis of Nonsense Aspect and Semantic Relations in Alice in Wonderland and Through the Looking Glass - Rahimi Alishah, Akbar; Hammoodi, Samira (International Journal of Psychosocial Rehabilitation, 2020)
Carroll’s Alice books are a rarity of nonsense literature, entertaining all generations. Carroll presents different philosophical ideas to urge people to think about the deep meaning of the English language and the function of literature. This article focuses on the concept of the sense, nonsense, and semantic relations in both Alice in Wonderland and Through the Looking Glass. Carroll conveys his journey to an imaginary world by Alice to transfer a reader to an unreal world. Several events in this work reflect the fact that the author’s reality is boring. The purpose of this article is to analyze the text of “Alice in Wonderland” and “Through the Looking Glass” through semantic relations such as homonymy, homophony, ambiguity, synonymy, antonyms, polysemy, hyponymy, contradiction, and the meaning of sense and nonsense. This article provides the reader with the meaning of language in both Alice in Wonderland and Through the Looking Glass and how the author plays in these semantic relations in order to show the impact of the nonsense and rational ambiguity to convey the reader into an imaginary world while showing the power of the word.